Delta EC Simulation on Influence of Resonator Length in Close-Open Standing Wave Thermoacoustic Engine - Anugrah, Rinasa Agistya; Wisnujati, Andika; Anggara, Fajar (Proklamasi 45 University, 2023)
Many applications of thermoacoustic engines in engineering. With its pressure of it, the energy can be harvested and can be converted to many other needs of energies like electrical energy. Energy in thermal form is converted to become acoustic energy and subsequently used to activate a bidirectional turbine. The resonator is very influential toward the power of the thermoacoustic engines. Simulation study with Delta EC fit to make predictions acoustic power as representative performance in thermoacoustic engine with close-open type and standing wave of oscillation. In this study, the material of the resonator is made from a stainless-steel duct with a diameter size of 50.8 mm with three variations of the length. The Standing-Wave Thermoacoustic Engine (SWTE) generates acoustic energy from a temperature gradient of 315 – 993 K. In this simulation, Acoustic Power decreased when the resonator length was extended. The shortest resonator had an acoustic power of 50.4 W, and the longest resonator had an acoustic power of 35.7 W.